A real-world comparison of outcomes between fractional flow reserve-guided versus angiography-guided percutaneous coronary intervention. - Christopher C Y Wong; Austin C C Ng; Cuneyt Ada; Vincent Chow; William F Fearon; Martin K C Ng; Leonard Kritharides; Andy S C Yong (PLoS ONE, 2021)
Background Fractional flow reserve (FFR)-guided percutaneous coronary intervention (PCI) has been shown to be superior to angiography-guided PCI in randomized controlled studies. However, real-world data on the use and outcomes of FFR-guided PCI remain limited. Thus, we investigated the outcomes of patients undergoing FFR-guided PCI compared to angiography-guided PCI in a large, state-wide unselected cohort. Methods and results All patients undergoing PCI between June 2017 and June 2018 in New South Wales, Australia, were included. The cohort was stratified into the FFR-guided group when concomitant FFR was performed, and the angiography-guided group when no FFR was performed. The primary outcome was a combined endpoint of death or myocardial infarction (MI). Secondary outcomes included all-cause death, cardiovascular (CVS) death, and MI. The cohort comprised 10,304 patients, of which 542 (5%) underwent FFR-guided PCI. During a mean follow-up of 12±4 months, the FFR-guided PCI group had reduced occurrence of the primary outcome (hazard ratio [HR] 0.34, 95% confidence intervals [CI] 0.20-0.56, P<0.001), all-cause death (HR 0.18, 95% CI 0.07-0.47, P = 0.001), CVS death (HR 0.21, 95% CI 0.07-0.66, P = 0.01), and MI (HR 0.46, 95% CI 0.25-0.84, P = 0.01) compared to the angiography-guided PCI group. Multivariable Cox regression analysis showed FFR-guidance to be an independent predictor of the primary outcome (HR 0.45, 95% CI 0.27-0.75, P = 0.002), all-cause death (HR 0.22, 95% CI 0.08-0.59, P = 0.003), and CVS death (HR 0.27, 95% CI 0.09-0.83, P = 0.02). Conclusions In this real-world study of patients undergoing PCI, FFR-guidance was associated with lower rates of the primary outcome of death or MI, as well as the secondary outcomes of all-cause death and CVS death.